Barriers and challenges of an outsource hospital foodservice operation: a narrative thematic analysis - Osman, Noor Suzana; Md Nor, Norazmir; Md Sharif, Mohd Shazali; Rahamat, Syafiqah; Abdul Hamid, Syahrul Bariah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: Hospital foodservice is one of the key performance metrics that should be constantly monitored to maintain and improve the quality of hospital services. However, hospital foodservice must overcome obstacles and constraints that can impact the quality of services supplied. This study explored the barriers and challenges foodservice employees encountered during food production and serving meals to patients. Methods: A qualitative study was conducted with thirteen foodservice employees (N = 13) at a government hospital in Selangor, Malaysia, that outsourced its foodservice operations. The interviewees were chosen based on inclusion and exclusion criteria. The interviews were audiotaped, transcribed, and analyzed using narrative, and thematic analysis. Results: The narrative findings reported foodservice employees were able to define their job in the foodservice department and describe their responsibilities in delivering sufficient quality of service to patients. The findings showed foodservice staff confronts barriers and challenges related to the type of foodservice operation, budget allocation, menu served, employee issues, meal preparation, and equipment. Employees also proposed that the government should regularly revise the foodservice contract specifications, budget allocation, and upgrade the equipment used during meal preparation and delivery to patients for future improvement. Conclusion: Future studies should be conducted in different hospital settings, including government, semi-government and private hospitals or foodservice operation systems such as in-house and outsourced operations or centralized and decentralized plating systems to explore other barriers and challenges that may affect the overall foodservice performance. Therefore, intervention studies can be proposed to improve their operation in the future.